Can Funds of Knowledge contribute to the involvement of Roma families in schools? Basis for an educational Project - Mar LORENZO MOLEDO; Gabriela MÍGUEZ SALINA; Francisco CERNADAS RÍOS (Teoría de la educación, 2020)
The Funds of Knowledge approach, whose anthropological origins date back to the study of trust relationships between Mexican households constituted on the border with the US, has established itself in many countries as an effective model for working with families at risk of social exclusion. It involves collecting family and cultural resources and turning them into knowledge that can be incorporated into schools. This paper is aimed at studying the Funds of Knowledge as a theoretical framework for the design of socio-educational programs, which encourage the involvement of Roma families in their children’s education. To this end, we use a descriptive methodology based on the analysis of the main theoretical studies carried out on the subject both nationally and internationally, specifically in North America, where this approach has already had a recognized trajectory. The results show the suitability of the Funds of Knowledge of Roma families as a basis for the design of proposals for inclusive education. This type of education promotes their involvement in the education of their children, thereby promoting their chances of educational success. Under these considerations, the respect for their history and bringing their voices into the political and social ideology must be taken into account, in order to improve relationships between family and school and, along with it, the academic performance of students, recognizing their role as subjects of rights, with the purpose of promoting greater inclusion of the Roma community in schools.